Xanthogranulomatous Salpingo-Oophoritis Presenting as an Ovarian Malignancy - Manandhar, Tara (Cureus, 2021)
Xanthogranulomatous salpingo-oophoritis is an extremely rare entity. The clinical features are similar to the common benign and malignant adnexal diseases, making it difficult to diagnose. Here we present a case of pelvic mass with high level of tumor markers who was operated with suspicion of adnexal tumor. Histopathology revealed it to be a case of xanthogranulomatous salpingo-oophoritis.